The Emergence of the New P.4 Lineage of SARS-CoV-2 With Spike L452R Mutation in Brazil - Bittar, Cíntia; Possebon, Fábio Sossai; Ullmann, Leila Sabrina; Geraldini, Dayla Bott; da Costa, Vivaldo G.; de Almeida, Luiz G. P.; da S. Sanches, Paulo Ricardo; Nascimento-Júnior, Nailton M.; Cilli, Eduardo M.; Artico Banho, Cecília; Campos, Guilherme R. F.; Ferreira, Helena Lage; et al. (Frontiers in Public Health, 2021)
The emergence of several SARS-CoV-2 lineages presenting adaptive mutations is a matter of concern worldwide due to their potential ability to increase transmission and/or evade the immune response. While performing epidemiological and genomic surveillance of SARS-CoV-2 in samples from Porto Ferreira—São Paulo—Brazil, we identified sequences classified by pangolin as B.1.1.28 harboring Spike L452R mutation, in the RBD region. Phylogenetic analysis revealed that these sequences grouped into a monophyletic branch, with others from Brazil, mainly from the state of São Paulo. The sequences had a set of 15 clade defining amino acid mutations, of which six were in the Spike protein. A new lineage was proposed to Pango and it was accepted and designated P.4. In samples from the city of Porto Ferreira, P.4 lineage has been increasing in frequency since it was first detected in March 2021, corresponding to 34.7% of the samples sequenced in June, the second in prevalence after P.1. Also, it is circulating in 30 cities from the state of São Paulo, and it was also detected in one sample from the state of Sergipe and two from the state of Rio de Janeiro. Further studies are needed to understand whether P.4 should be considered a new threat.